Implantoplasty Improves Clinical Parameters over a 2-Year Follow-Up: A Case Series - Martins, Orlando (2022)
Background and Objectives: Peri-implantitis treatment is still undefined. Regenerative treatment is expensive and technically demanding due to the need to handle biomaterials, membranes and different methodologies of decontamination. Resective treatment and implantoplasty might be a viable solution. This case series presents a 24 month retrospective observational study of 10 peri-implantitis patients treated with implantoplasty. Materials and Methods: In the present case series, 10 peri-implantitis patients (20 implants) were treated with a resective approach and implantoplasty. Previous to implantoplasty, all patients underwent non-surgical treatment. This surgery consisted in a full-thickness flap and implant surface exposure. The exposed non-osseointegrated implant body was submitted to implantoplasty. The flap was apically repositioned and sutured. Patients were accompanied for 24 months. Results: The mean initial probing depth (PD) (PD = 5.37 ± 0.86 mm), bleeding on probing (BoP = 0.12 ± 0.06%) and suppuration (Sup = 0.01 ± 0.01%) decreased significantly at the 12 month evaluation (PD = 2.90 ± 0.39 mm; BoP = 0.01 ± 0.01% and Sup = 0.00 ± 0.00%). Between the 12 and 24 month evaluations, there were no significant clinical changes (PD = 2.85 ± 0.45 mm; BoP = 0.01 ± 0.01% and Sup = 0.00 ± 0.00%). Mucosal recession (MR) had a significant increase between the baseline and the first 12 months (0.69 ± 0.99 mm vs. 1.96 ± 1.33 mm), but there were no significant changes between the 12th and 24th month (1.94 ± 1.48 mm). The success rate was 100% without implant fracture or loss. Conclusions: Resective surgery and implantoplasty might be a valid option in some specific peri-implantitis cases. Properly designed clinical trials are needed to confirm this possibility.